The Influence of Father Involvement on the Responsible Attitudes of Children Aged 5-6 Years - Mardhiyyah, Inda Rabbi; Puspitasari, Intan; Muarifah, Alif; Maharani, Ega Asnatasia (Jurnal Pendidikan Anak, 2025)
The purpose of this study was to determine whether there is an influence of father involvement on the responsible attitudes of children aged 5–6 years. Using a correlational quantitative approach, 96 fathers were randomly selected from a population of 429 fathers in Medan Tuntungan District. The instruments used were a father involvement questionnaire based on Pleck's theory (2010) and a child responsibility attitude questionnaire from Harris & Bean (2001). Data were analyzed using simple linear regression techniques, which revealed a significant relationship between father involvement and children's sense of responsibility, with a correlation coefficient (R) of 0.737 and a coefficient of determination (R²) of 0.544. This indicates that father involvement contributes 54.4% to the development of children's sense of responsibility at an early age. These findings emphasize the importance of the father's role, not only physically but also emotionally, in parenting. The researchers recommend educational programs and systematic support for fathers to better understand their role in fostering children's responsibility from an early age. Such support can contribute to more optimal social-emotional development in children.